Preventing dance injuries: current perspectives - Russell JA (Dove Medical Press, 2013)
Jeffrey A Russell Division of Athletic Training, School of Applied Health Sciences and Wellness, Ohio University, Athens, OH, USA Abstract: Dancers are clearly athletes in the degree to which sophisticated physical capacities are required to perform at a high level. The standard complement of athletic attributes – muscular strength and endurance, anaerobic and aerobic energy utilization, speed, agility, coordination, motor control, and psychological readiness – all are essential to dance performance. In dance, as in any athletic activity, injuries are prevalent. This paper presents the research background of dance injuries, characteristics that distinguish dance and dancers from traditional sports and athletes, and research-based perspectives into how dance injuries can be reduced or prevented, including the factors of physical training, nutrition and rest, flooring, dancing en pointe, and specialized health care access for dancers. The review concludes by offering five essential components for those involved with caring for dancers that, when properly applied, will assist them in decreasing the likelihood of dance-related injury and ensuring that dancers receive optimum attention from the health care profession: (1) screening; (2) physical training; (3) nutrition and rest; (4) specialized dance health care; and (5) becoming acquainted with the nature of dance and dancers. Keywords: dance, injuries, injury prevention, fitness, wellness, health